Nation Building and Regional Integration: The Triplex Confinium - Roksandić, Drago (2007)
The workshop was supposed to clarify regional contexts of nation building processes in modern Europe. This particular contribution was dealing with the complex case of nation building processes among Croats, Serbs and Boshnyiaks in regions they were intermingling with each other, mostly in the Triplex Confinium area in its largest sense.
The workshop was organized by the Centre for the Study of Cultural Forms of Modern European Politics, The University of Manchester
Projekt MZOS
ENG